Peran Islam dalam Membangun Karakter dan Pendidikan Budaya Melayu - Fariati, Betti; Riadi, Haris; Norafiza, Norafiza; Nur'aina, Nur’aina (LPPM Institut Pendidikan Nusantara Global, 2025)
Islam plays a central role in shaping and coloring Malay culture, including dimensions of education, morality, law, and customs. This study uses a descriptive qualitative approach with a literature study method to examine how Islam influences Malay culture over time and the challenges faced in maintaining these values ​​in the modern era. Historical research shows that Islam entered the archipelago through trade, preaching, and marriage, which then brought about significant transformations in the traditional Malay education system. Institutions such as surau, madrasah, and pesantren became centers of religious education that not only taught Islamic knowledge, but also shaped the character and morality of the community. Islamic moral values ​​were integrated into the social norms and behavior of Malay society, strengthening manners, ethics, and moral principles in everyday life. In addition, Malay customary law underwent Islamization by adopting various sharia principles in its legal practices. However, the development of the era, the flow of globalization, and technological advances have become major challenges in maintaining this Islamic cultural heritage. Therefore, strategic efforts are needed through contextual transformation of Islamic education, utilization of digital media as a means of preaching and education, and strengthening the role of the family and social environment as a fortress of Islamic values. This study concludes that the sustainability of Islamic values ​​in Malay culture is highly dependent on the ability of society to adapt and revitalize these values ​​so that they remain relevant in the dynamics of modern life.